2016
DOI: 10.1108/ijmce-06-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the development and professional growth of middle space educational leaders through mentoring

Abstract: Purpose – The purpose of this paper is to introduce readers to the special issue on “middle space” education leaders (those individuals who are second-in-command in schools). The special issue contains papers pertaining to mentoring those preparing for and aspiring to the assistant school leader role, as well as papers on programs that support new assistant principals/vice-principals through mentoring and coaching. The authors provide background on middle space leadership and mentoring from exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…From the above principles, it can be concluded that the activities of professional learning must be grounded in the multicultural context that promotes collaborative interaction, shared discussion, expands professional knowledge of sociocultural dimensions, cultural perspectives and the practices of professional learning. This is in line with Searby and Armstrong’s (2016) recommendation of the importance of mentoring and coaching in school leadership development. In fact, mentoring and coaching aspire racialized teachers to be more open to the cultural school environment.…”
Section: The Implication To Teacher Professional Developmentsupporting
confidence: 89%
“…From the above principles, it can be concluded that the activities of professional learning must be grounded in the multicultural context that promotes collaborative interaction, shared discussion, expands professional knowledge of sociocultural dimensions, cultural perspectives and the practices of professional learning. This is in line with Searby and Armstrong’s (2016) recommendation of the importance of mentoring and coaching in school leadership development. In fact, mentoring and coaching aspire racialized teachers to be more open to the cultural school environment.…”
Section: The Implication To Teacher Professional Developmentsupporting
confidence: 89%
“…In the second case, it is a matter of being in training that is not only cultural, as teachers are also mentors. 22 Additionally, teachers contribute to personal growth and the sphere of values. If health care professionals and teachers are mobbing victims, then the consequences also spill over into the quality of their work, creating a difficult or tense climate.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA and other countries, increasingly, principal preparation programs and school districts are utilizing leadership coaches to help grow and sustain high-quality school leaders (Barnett and O'Mahony, 2013; Fletcher and Mullen, 2012; Rhodes and Fletcher, 2013). There is strong consensus among scholars that coaching is an exemplary feature of leadership onboarding and ongoing capacity development for practicing assistant principals and principals (Barnett and O'Mahony, 2013; Bickman et al , 2012; Cardno and Youngs, 2013; Crow and Whiteman, 2016; Duncan et al , 2011; Farver and Holt, 2015; Forde et al , 2013; Goff et al , 2014; Gordon et al , 2016; Huff et al , 2013; Knight, 2006; Liang and Augustine-Shaw, 2016; Schön, 1983; Searby et al , 2016). Coaching is viewed as effective because it helps aspiring leaders internalize their learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response, more and more principal preparation programs across the USA have intentionally transitioned from conventional, course-based programming to more comprehensive models. These include practice, or field-based leadership development, in the form of principal internships, with coaching (Baron and Haller, 2010) and reflective practice (Orr, 2006) for leaders who, upon entry into administration, usually first occupy “middle space” leadership positions, such as assistant principals (Searby and Armstrong, 2016). Characteristics of highly effective principal preparation programs include authentic learning through field-based experiences, along with individualized coaching (Fletcher and Mullen, 2012; Jackson and Remer, 2014).…”
Section: Introductionmentioning
confidence: 99%